STRATEGI PENINGKATAN PRODUKTIVITAS PERIKANAN SKALA KECIL BERKELANJUTAN DI KABUPATEN ACEH BARAT PROVINSI ACEH - Teuku Amarullah; Mohamad Gazali (JURNAL PERIKANAN TROPIS, 2019)
The strategy of productivity improvement of sustanable small-scale capture fisheries in West Aceh, Aceh Province was urgent for fisheries management. This research have been conducted for three months to begin from May until  July 2018. The aims of this study is to determine factors that affected Productivity improvment of sustanable small-scale capture fisheries and to develop strategies for improving productivity of sustanable small-scale capture fisheries in Aceh Barat, Aceh Province. The method used is a survey and study of literature. In addition to use a method of interview to social respondents. Data analysis methods are linear regression, descriptive and SWOT analysis. Results showed factors affected productivity of sustanable small-scale capture fisheries in Aceh Barat is capital, number of labour and the kinds of cpture boat.  While other factors such as the trip, age and level of college are  no effect. The strategy of increasing the productivity of sustanable small-scale fisheries in improving economy of fishermen in Aceh Barat district that can be applied: give subsidy, catching fleet and fishing and fishing equipment, financial management training, and financial institusional to provide alternative working for small-scale fisheries